Anchorman. 2 : the legend continues [videorecording (DVD)] - McKay, Adam, 1968-; Ferrell, Will, 1967-; Ferrell, Will, 1967-; Applegate, Christina, 1971-; Rudd, Paul; Koechner, David, 1962-; Carell, Steve, 1962- (Paramount, 2014)
Ron and Veronica's romance falls apart as the duo anchors a weekend broadcast at a New York-based network in 1980. Ron is fired for being the worst anchor anyone has ever seen and so he leaves Veronica rather than live in her shadow. So he re-creates himself at a CNN-type network in the eighties and accidentally invents the soul-sucking brand of non-news that now rules cable as he tries to win back Veronica's love.